CISG Advisory Council Opinion No. 7 I. Exemption of Liability for Damages Under Article 79 of the CISG - Alejandro M. Garro (Nordic Journal of Commercial Law, 2008)
CISG Advisory Council Opinion No. 7 I. Exemption of Liability for Damages Under Article 79 of the CISG